Food, identity, power and multicultural solidarity in Preeta Samarasan’s Tale of a Dreamer’s Son - Wan Putri Nurlisa Jaafar; Nor Fariza Mohd Nor; Ravichandran Vengadasamy; Melissa Shamini Perry (Penerbit Universiti Kebangsaan Malaysia, 2025)
The role of food from a sociocultural perspective is one that has been increasingly explored in cultural narratives and academic inquiry in the past few decades. In literature, food is used as a tool to evoke the senses and convey meaning about identity, culture, relationships and emotions. Food can be instrumental in shaping personal and cultural identities, community dynamics and embedding ideologies, particularly in culturally diverse societies. This article explores the intersections of food and identity in multicultural Malaysia as depicted in Preeta Samarasan's novel Tale of the Dreamer's Son. Through critical literary analysis of the novel, the article examines how food shapes identities and functions as a tool for manifesting belief systems, cultural practices and power as well as how it fosters the Malaysian concept of Muhibbah (the spirit of multicultural solidarity and mutual respect) within the multicultural landscape of Malaysia. Anderson’s (2006) theory of Imagined Communities and the concept of muhibbah as framed by Haslina Ibrahim (2013) is applied to understand how identity, power and solidarity are at work through food consumption practices, as well as the restrictions and regulations surrounding food, within the context of multicultural Malaysia, as depicted in the novel. The analysis reveals that food is used as a marker of personal and communal identity and relationship dynamics in the novel. Food also serves as an ideological tool to impart and manifest values and belief systems as well as power in a diverse society. This study contributes to the broader discourse on food, identity, and gastronativism in literature and highlights the unique interplay between culinary practices and sociocultural dynamics in multicultural contexts.